Improve the Quality of Life of Women and Reduce Clinical and Morphological Features of Endometriosis under the Influence of Dienogest Preparation - Akter, Mst Jesmin; Rahman, Fatema; Iqbal, Abul Basher Mohammed (Journal of Comilla Medical College Teachers’ Association, 2024)
Background: the aim of our study was to analyze the effect of dienogest on the endometroid glands in the myometrium. A transvaginal sonographic morphologic assessment of the effect of the drugs, taking into account its safety, as well as as an assessment of changes in the quality of life of women associated with decreases in the severity symptoms of adenomyosis and endometriosis. Objectives: To evaluate the effectiveness of Dienogest in improving quality of life to reduce clinical manifestation of adenomyosis. Methods: It is a randomized control study conducted from January 2022 to December 2023 that included women aged 20-50 years, which is diagnosed as adenomyosis by clinical presentation manifested by the presence of pelvic pain, abnormal uterine bleeding, painful, and or heavy menstruation, as well as the presence of anemia and transvaginal sonography. Patients were divided into 3 groups depending on the name of the drugs that they used. 20 patients of group 1 received the drug “dienogest” at 2 mg/day for 6 months. The second group received the combined oral contraceptive drug, “Marvelon “which contains estrogen and progesterone. The third group included 20 patients who received only progesterone “medroxy”10 mg continuously for 6 months. Result: After the starting of drugs for 6-12 months bloody discharge from the genital tract in group 1 completely stopped in all 8 women. In group ii, the discharge decreased in 3 women and completely stopped in 6 women. In group iii, the discharge decreased in 3 women and completely stopped in 5 women. pain in group 1 completely stopped in 5 women out of 6(83.3%) and 2 women decreased pain out of 6 (33.4%) in the second group the pain stopped completely in 6 women out of 10 (58.3%) and decreased in 4 women out of 10 (34.66%). In the third group, pain completely recovered in 6 out of 10 (60%) and decreased in 4 women out of 10 (40%). According to transvaginal sonographic evidence of myometrium with endometroid glands before treatment, group 1 had 12.2± 3.8 glands before treatment and 1.4 ± .8 after treatment. In the second group, the number of glands before treatment was 10.8 ±1.4 and after treatment 3.8 ±.7 glands. in the third group before treatment, 6.7 ± 2.1 endometroid glands were determined and after treatment 2.7 ±1.4 glands in the field of view. Conclusion: Dienogest is effective in the treatment of endometriosis and reduces both the clinical manifestations of adenomyosis (abnormal uterine bleeding and chronic pelvic pain) and increases hemoglobin levels, together with a decrease in the activity of the endometroid glands in the myometrium. Dienogest is highly selective progesterone against progesterone receptors and has anti-proliferative activity in isolated human endometrial cells. Given the indicators of the 25-item short-form survey questionnaire, the quality of life in all the studied groups improved in all parameters, which indicates the effectiveness of the dienogest-containing drugs used. J Com Med Col Teachers Asso July 2024; 28(2): 65-69